Gender equality indicators in higher education: SDG 5 perspective and bioethical approach - Carlotto, Ivani Nadir (2020)
In this topic, the objective is to identify and clarify the concepts predominantly used in this article, so that they can make sense and be understood in the context of gender equality in the higher education. Therefore, the most used terms include Bioethics is an area of inter and transdisciplinary study that involves Ethics and Biology, based on the ethical principles that govern life and its ethical dilemmas, emerging as a reflexive response on human interactions in society and in their environments. The bioethical principles are the model of bioethical analysis traditionally used and of great application in clinical practice in most countries is the principalist, introduced by Beauchamp and Childress (1979). These authors propose four fundamental bioethical principles: autonomy, beneficence, non-maleficence, and justice, in a prima facie sense. However, these principles can be expanded according to the bioethical line adopted in a given reality, to obtain a reflection on an ethical dilemma. The gender equality is the concept that defends social equivalence between the sexes, with equal opportunities for men and women. Gender equity, in turn, refers to equity in treatment for women and men, according to their respective needs. It is important to clarify the concept surrounding the Sustainable Development Goals of the 2030 Agenda (SDG). These Goals are a collection of 17 global goals designed to be a model for achieving a better and more sustainable future for everyone. The SDGs, established in 2015 by the United Nations General Assembly and expected to be reached by 2030, are part of UN Resolution 70/1, the 2030 Agenda.